1999
DOI: 10.1161/01.cir.100.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prophylactic Immediate Posttransplant Ganciclovir on Development of Transplant Atherosclerosis

Abstract: TxCAD incidence appears to be lower in patients treated with ganciclovir who are not treated with calcium blockers. Given the limitations imposed by post hoc analysis, a randomized clinical trial is required to address this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(142 citation statements)
references
References 15 publications
4
135
0
3
Order By: Relevance
“…For example, Lemstrom et al demonstrated that prophylactic administration of ganciclovir, a drug that inhibits viral replication, entirely abolishes the accelerating effect of rat CMV infection on CAV in immunosuppressed and nonimmunosuppressed rat recipients (49). We have reported similar findings in heart transplant recipients, showing patients who received prophylactic treatment with ganciclovir during the initial 28 days after transplantation, had a significantly lower prevalence rate of CAV diagnosed by coronary angiography, compared with placebo (50). It should be emphasized that this cohort of patients received antilymphocyte antibody therapy as part of their routine immunosuppressive regimen early after transplant, a practice that has been shown to increase the rate of CMV activation and disease.…”
Section: Evidence From Therapeutic Trialssupporting
confidence: 67%
“…For example, Lemstrom et al demonstrated that prophylactic administration of ganciclovir, a drug that inhibits viral replication, entirely abolishes the accelerating effect of rat CMV infection on CAV in immunosuppressed and nonimmunosuppressed rat recipients (49). We have reported similar findings in heart transplant recipients, showing patients who received prophylactic treatment with ganciclovir during the initial 28 days after transplantation, had a significantly lower prevalence rate of CAV diagnosed by coronary angiography, compared with placebo (50). It should be emphasized that this cohort of patients received antilymphocyte antibody therapy as part of their routine immunosuppressive regimen early after transplant, a practice that has been shown to increase the rate of CMV activation and disease.…”
Section: Evidence From Therapeutic Trialssupporting
confidence: 67%
“…In recipients of heart transplants, treatment with ganciclovir, a potent inhibitor of viral replication and CMV disease, delayed the time to allograft rejection (Merigan et al 1992). A subsequent post-hoc analysis of these data confirmed that prophylactic ganciclovir treatment delayed graft rejection compared to controls (Valantine et al 1999). Moreover, the early control of sub-clinical HCMV replication after cardiac transplantation by T-cell immunity reduces allograft TVS and CR (Tu et al 2006).…”
mentioning
confidence: 80%
“…In contrast, another study failed to obtain a difference between renal transplant recipients with and without diabetes in terms of graft loss [19]. It could be likely, that either a follow-up period of 10 years is too short or our immunosuppressive protocol per se delays to a certain extent the development of atherosclerosis in coronary arteries [15,20,21,22].…”
Section: Discussionmentioning
confidence: 98%